Dendrobium officinale polysaccharide regulates the immune function of raw264.7 cells via the nf-κb and mapk signaling pathways - Guangpei XU; Yanfei HE; Ping JIANG; Lei YANG; Jianwen CAO; Chuanbo SUN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2025)
To investigate the immunomodulatory effects of Dendrobium officinale polysaccharide (DOP) on RAW264.7 macrophages. DOP was purified from Dendrobium officinale using water extraction-alcohol precipitation and gel column chromatography. The molecular weight distribution of the polysaccharide was analyzed by high-performance gel permeation chromatography (HPGPC). The effects of DOP on RAW264.7 cells were evaluated as follows: cell viability was assessed via MTT assay to screen appropriate treatment concentrations; ELISA was used to detect the secretion of inflammatory cytokines (IL-10, IL-12 p40, and IL-6); RT-qPCR was employed to measure the expression of inflammatory genes (IL-1β, IL-10, IL-12 p40, and IL-6); and Western blotting was performed to analyze the expression of P65, phosphorylated P65 (p-P65), JNK, phosphorylated JNK (p-JNK), ERK, and phosphorylated ERK (p-ERK). The purified DOP exhibited a yield of 8.24% and a total sugar content of 95.33±3.11%. HPGPC analysis revealed three peaks corresponding to molecular weights of 1.89 x 10⁵ Da, 549 Da, and 211 Da. DOP showed no cytotoxicity toward RAW264.7 cells at concentrations ranging from 3.125 to 400 μg/mL. All tested concentrations of DOP significantly enhanced the mRNA expression of IL-1β, IL-10, IL-12 p40, and IL-6 (P<0.05, P<0.01, P<0.001) and promoted the secretion of IL-10, IL-12 p40, and IL-6 in a dose-dependent manner. Regarding the NF-κB and MAPK signaling pathways, DOP markedly increased the expression of p-JNK, p-ERK, and p-P65 proteins (P<0.001), with sustained effects observed for up to 120 minutes (P<0.001). DOP activates RAW264.7 cells by promoting inflammatory gene expression, stimulating cytokine secretion, and triggering the NF-κB and MAPK pathways, thereby exerting immunomodulatory effects.